Dual-Mechanism Gastroretentive Tablets with Encapsulated Gentian Root Extract - Jelena Mudrić; Ljiljana Đekić; Nemanja Krgović; Đorđe Medarević; Katarina Šavikin; Milica Radan; Nada Ćujić Nikolić; Tijana Ilić; Bojana Vidović; Jelena Đuriš (Pharmaceutics)
Background/Objectives: This study aimed to develop gastroretentive tablets based on mucoadhesive–floating systems with encapsulated gentian (Gentiana lutea, Gentianaceae) root extract to overcome the low bioavailability and short elimination half-life of gentiopicroside, a dominant bioactive compound with systemic effect. The formulation also aimed to promote the local action of the extract in the stomach. Methods: Tablets were obtained by direct compression of sodium bicarbonate (7.5%) and solid lipid microparticles (92.5%), which were obtained with lyophilizing double emulsions. A quality by design (QbD) was employed to evaluate the impact of formulation factors and processing parameters on emulsion viscosity, powder characteristics (moisture content, encapsulation efficiency, flowability), and tablet characteristics (floating lag time, gentiopicroside release, and assessment of dispersibility during in vitro dissolution). Results: The trehalose content and high-shear-homogenization (HSH) time of primary emulsion were critical factors. Trehalose content positively influenced emulsion viscosity, moisture content, floating lag time, encapsulation efficiency, and the release rate of gentiopicroside. HSH time positively affected powder stability and negatively gentiopicroside release. The selected powder had a high gentiopicroside encapsulation efficiency (95.13%), optimal stability, and good flowability. The developed tablets exhibited adequate floating lag time (275 s), mucoadhesive properties, and gentiopicroside biphasic release (29.04% in 45 min; 67.95% in 6 h). Furthermore, the optimal tablet formulation remained stable for 18 months and was primarily digested by duodenal enzymes. Conclusions: Dual-mechanism gastroretentive tablets with encapsulated gentian root extract were successfully developed. The in vitro digestion study demonstrated that the optimal formulation effectively resisted gastric enzymes, ensuring the release of its contents in the small intestine, even in the case of premature gastric evacuation.